Beyond Business: A Poster Contrasting CEO Activism on Social Media in India and the United States - Arya, Arshia; Rashid Shora, Shehla; Pal, Joyojeet (The Compass, 2021)
We studied the Twitter activity of business leaders of top 250 companies in India and the US between January, 2019 and May, 2021 and looked for trends related to cause-related messaging through a topical analysis of their tweets. Using a Word2Vec bag of words model for textual classification, we quantified their engagement with socio-political messaging, using keywords related to the United Nations Sustainable Development Goals (UN SDGs). We found that messaging on themes that have widespread social purchase and are not politically sensitive is relatively comparable across the two countries, but that results differ vastly on issues of political sensitivity. Our results point at the complex relationship between business and politics in the two countries, and the growing importance of social media in signalling those. We conclude by pointing out the importance of these findings for political science and policy research and by highlighting the scope for future work in this area.